Old beginnings exhibit brochure - Unidentified author (Colorado State University. Libraries, 1987)
Brochure of "Old Beginnings" exhibit held in the Gustafson Gallery. Contains biography of Dagmar C. Gustafson, dedication lineup, and information about the Gustafson Gallery.
Keywords: Fashion -- History; Fashion -- Exhibitions